Molecular docking reveals critical residues in Candida albicans Cyr1 for peptidoglycan recognition and hyphal growth - Ng, Allan Wee Ren (2023)
The key virulent characteristic of Candida albicans, the major fungal pathogen in humans, lies in its ability to switch between the benign yeast state and the invasive hyphal form upon exposure to specific stimuli. Among the numerous hyphal-inducing signals, bacterial peptidoglycan fragments (PGNs) represent the most potent inducers of C. albicans hyphal growth. The sole adenylyl cyclase Cyr1 in C. albicans is a known sensor for PGNs and activates downstream signaling of hyphal growth, yet the molecular details of PGN-Cyr1 interactions have remained unclear. In this study, we performed in silico docking of a PGN motif to the modeled structure of the Cyr1 leucine-rich repeat (LRR) domain and uncovered four putative PGN-interacting residues in Cyr1_LRR. The critical roles of these residues in PGN binding and supporting C. albicans hyphal growth were demonstrated by in-gel fluorescence binding assay and hyphal induction assay, respectively. Remarkably, the C. albicans mutant harboring the cyr1 variant allele that is defective for PGN recognition exhibits significantly reduced cytotoxicity in macrophage infection assay. Overall, our work offered important insights into the molecular recognition of PGNs by C. albicans Cyr1 sensor protein, establishing that disruption of PGN recognition by Cyr1 results in defective hyphal growth and reduced virulence of C. albicans. Our findings provide an exciting starting point for the future development of Cyr1 antagonists as novel anti-virulence therapeutics to combat C. albicans invasive growth and infection.